“Kekerasan Dapat Dimaknai Berbeda-Beda”: Ragam Pemaknaan atas Kekerasan Terhadap Perempuan dalam Praktik Gerakan Sosial Aliansi Laki-Laki Baru - Ramadhan, Febi Rizki (Paradigma: Jurnal Kajian Budaya, 2017)
This article examines the variety of meaning towards violence against women in Aliansi Laki-laki Baru’s social movement practice as a social movement that focuses on issues regarding male engagement in ending violence against women and achieving gender equality. Using ethnographic methods, I argue that social movement, particularly Aliansi Laki-laki Baru, could not be understood as monolithic and homogeneous entity because its participants could have various meanings on violence against women. While violence against women could be contextualized as Aliansi Laki-laki Baru’s main focus, participants in ALB could construct their own meaning on ‘violence against women’ as a sociocultural phenomenon. Furthermore, I argue that the variety of meaning towards issue on violence against women could be caused by ALB’s participants’ subjectivity and their own personal experiences.